Development of Artificial Intelligence in China - Wei, Meilan; Noyjarean , Nopparat; Thiensawangchai , Supisara (International Journal of Multidisciplinary in Management and Tourism, 2026)
This study aims to investigate the developmental trajectory of Artificial Intelligence (AI) in China to construct a historical periodization and analyze the evolution of AI applications across key sectors. Employing a qualitative documentary analysis method based on government policy papers, industry reports, and patent data from 1978 to 2025, the research examines the interplay between state strategies and technological breakthroughs. The findings categorize China’s AI development into four distinct phases: the Initial Stage (1978–2000), Developmental Emergence (2000–2012), Expansion (2012–2015), and the Leapfrog Development Phase (2015–present). The analysis reveals that China’s rapid advancement is driven by robust state-led initiatives and private investment, resulting in significant implementation in service, agriculture, and legal sectors. However, despite leading in patent applications, challenges remain regarding core technology dependence (e.g., semiconductors) and the complexity of replacing high-skilled labor. The article concludes by discussing the implications of China's innovation model and future trends in AI governance.